(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2016)
A 80 years old diabetic, hypertensive with severe sleep apnoea syndrome male patient who is on BiPAP machine having history of repeated hospitalization in ICU for stroke, LVF,sleep apnoea and chronic urinary retension with repeated urinary catheterization with intake of different parenteral antibiotic therapy presented with burning micturation along with passage of cloudy urine for five days. His urine culture report revealed growth of Pseudomonus aeruginosa which was resistant to all antibiotics like Azithromycine, Cefixime, Ceftriaxone, Cefuroxime, Cotrimoxazole, Amoxyclav, Amikacin, Ceftazidime, Ciprofloxacin, Doxycyclin, Meropenem, Nitrofurantoin, Chloramphenicol, Cefipime, Tetracyclin, Cefpirome, Cefotaxime, Levofloxacin, Piperacilin+Tazobactam, Cefoperazone+Sulbatam, Tygicyclin, and Ticarcillin+Clamlanic acid except Colistin which was sensitive. Patient was given Inj. Colstin for seven days and then was stopped due to severe nephrotoxicity and microbiologically patient was cured. But two weeks after again growth of multidrug resistant pseudomonas occurred in his urine sample. Then patient was given a series of parenteral and oral antibiotics(Inj. Cefuroxime, Inj. Colistin, Inj. Ceftriaxone, Moxifloxacin, Levofloxacin, Azythromycin, Ciprofloxacin, cefixime, cotrimoxazole etc) to which the organism was resistant along with relieve of obstruction by urinary catheterization for last 12 months of study. At follow up after end of study patients well being was good though resistant organism remained in his urine sample proved by repeated urine culture where the colony count of the organism was not in pathological range. JCMCTA 2016 ; 27 (1) : 61 - 64